2008
DOI: 10.1016/j.ultrasmedbio.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Co-Encapsulate Gas and Drugs in Liposomes for Ultrasound-Controlled Drug Delivery

Abstract: A novel method for the facile production of gas-containing liposomes with simultaneous drug encapsulation is described. Liposomes of phospholipid and cholesterol were prepared by conventional procedures of hydrating the lipid film, sonicating, freezing and thawing. A single, but critical modification of this procedure generates liposomes that contain gas (air, perfluorocarbon, argon); after sonication, the lipid is placed under pressure with the gas of interest. After equilibration, the sample is frozen. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 25 publications
0
71
0
Order By: Relevance
“…16,22 ELIPs can contain air or a bioactive gas such as nitric oxide or xenon and have a mean diameter of less than 1 lm. [23][24][25] Compared with commercially available UCAs, the difference in ELIP size, shell composition, and gas content may impact the frequencydependent attenuation and backscatter coefficients. Consequently, the insonation parameters for imaging ELIPs in diagnostic ultrasound applications may be significantly different.…”
Section: Introductionmentioning
confidence: 99%
“…16,22 ELIPs can contain air or a bioactive gas such as nitric oxide or xenon and have a mean diameter of less than 1 lm. [23][24][25] Compared with commercially available UCAs, the difference in ELIP size, shell composition, and gas content may impact the frequencydependent attenuation and backscatter coefficients. Consequently, the insonation parameters for imaging ELIPs in diagnostic ultrasound applications may be significantly different.…”
Section: Introductionmentioning
confidence: 99%
“…In order to maximize the therapeutic efficacy, liposomes should display properties that both impart high US sensitivity (sonosensitivity) and favour drug retention in the blood stream, to enable sufficient tumour accumulation. Several studies have shown that gas-containing particles are highly sonosensitive (Huang et al, 2008;Unger et al, 1998;Huang and MacDonald., 2004). Unfortunately, gas-filled liposomes are micron-sized and thus too large to allow for effective extravasation into tumour tissue (Ferrara, 2008;Maeda et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a mixture of NO and argon at a ratio of 1:9 encapsulated under 9 atm pressure was utilized to produce a total volume of 45 µL ± 13 µL encapsulated into 5 mg of lipids. 33 Second, the average size of our ELIP is 800 nm. They can be conjugated with antibodies for targeted delivery.…”
Section: Discussionmentioning
confidence: 99%